Criminal Settlement Of Criminal Acts Of Motorcycle Theft By Child Through Restorative Justice - Chariri, Agus (International Journal of Educational Research & Social Sciences, 2022)
A criminal act is an unlawful behavior carried out by an individual and must be punished for the wrongdoing as stated in the law. Criminal acts committed by children or known as juvenile delinquency are now increasingly widespread and varied, both in frequency in quantity or in seriousness in quality in the form of crime. If child crime develops rapidly and widely, what happens is that children who commit crimes will grow into adults and have the potential to become criminals if there is no serious response early on. This study uses an approach with a normative juridical method with a descriptive analytical research specification. The data used is secondary data. Based on the research results, the conclusions in this study include 1) The factors that cause children to commit the crime of theft include internal factors (personality), environmental factors and economic factors. 2) Implementation of restorative justice in handling the crime of motorcycle theft which is in accordance with the Implementation of the Diversion Child Criminal Justice System Law Number 11 of 2012. In applying restorative/diversion justice, there are always efforts for every child who commits a crime. In some cases, diversion can be carried out with the consent of all parties, so that the case does not reach the prosecution level. Restorative justice only applies to petty crimes, with mediation through deliberation. The application of restorative justice has not been effective, because there are still people who fail to implement the purpose of diversion in the investigation of criminal cases of theft of children's motorcycles, especially the police have not implemented the purpose of restorative justice. Everything from the number of children who steal motorcycles. 3) Obstacles in overcoming the crime of motorcycle theft by children through restorative justice, namely the difference in perceptions related to the meaning of justice by restorative justice actors and the existence of an incosystem in the implementation of regulations, especially those regulated in article 7 paragraph (2) of law number 11 of 2012 about the juvenile criminal justice system.